Escherichia coli and Staphylococcus aureus: leading bacterial pathogens of healthcare associated infections and bacteremia in older-age populations. (3rd July 2018) - Poolman, Jan T.; Anderson, Annaliesa S.
ABSTRACT: Introduction : Bacteremia and healthcare-associated infections (HAIs) continue to rise in industrialized countries, in line with population aging and increased healthcare needs. Escherichia coli and Staphylococcus aureus are the most common pathogens causing HAIs and bacteremia. Areas covered : This review discusses risk factors in the healthcare setting contributing to the rise in bacteremia and other invasive bacterial HAIs in older populations in general, and attributed to E. coli and S. aureus . Treatment of infections is becoming increasingly difficult due to emerging antimicrobial resistance. Prophylactic vaccines may be the solution to lowering the burden of serious infections in the elderly. Expert commentary : E. coli and S. aureus vaccines routinely administered to older adults and to people undergoing prescheduled procedures with high infection risks could prevent a significant proportion of severe disease, and could potentially also limit the further emergence of antimicrobial resistance.